2020
DOI: 10.1002/ange.202011559
|View full text |Cite
|
Sign up to set email alerts
|

Host Differential Sensitization toward Color/Lifetime‐Tuned Lanthanide Coordination Polymers for Optical Multiplexing

Abstract: Optical multiplexing based on luminescent materials with tunable color/lifetime has potential applications in information storage and security. However, the available tunable luminescent materials reported so far still suffer from several drawbacks of low efficiency or poor stability, thus restraining their further applications. Herein, we demonstrate a strategy to develop efficient and stable lanthanide coordination polymers (LCPs) with tunable luminescence as a new option for optical multiplexing. Their mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…This process of RE sensitization for their characteristic emission is known as the "antenna effect". [34][35][36] Herein, we report a generalizable strategy for the synthesis of highly stable RE-MOFs with shp topology and 12-connected RE 9 clusters. By adjusting the dosage of the modulating reagent (2-fluorobenzoic acid), a total of 26 isostructural RE-MOFs, JNU-205-RE and JNU-206-RE (JNU = Jinan University; RE = Eu, Pr, Nd, Sm, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu and Y), were obtained with X-shaped tetracarboxylate linkers, 4,4′,4″,4′′′-benzene-2,3,5,6-tetrayl-tetrabenzoate (BTEB) and 4,4′,4″,4′′′-pyrazine-2,3,5,6-tetrayl-tetrabenzoate (BTTB).…”
Section: Introductionmentioning
confidence: 99%
“…This process of RE sensitization for their characteristic emission is known as the "antenna effect". [34][35][36] Herein, we report a generalizable strategy for the synthesis of highly stable RE-MOFs with shp topology and 12-connected RE 9 clusters. By adjusting the dosage of the modulating reagent (2-fluorobenzoic acid), a total of 26 isostructural RE-MOFs, JNU-205-RE and JNU-206-RE (JNU = Jinan University; RE = Eu, Pr, Nd, Sm, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu and Y), were obtained with X-shaped tetracarboxylate linkers, 4,4′,4″,4′′′-benzene-2,3,5,6-tetrayl-tetrabenzoate (BTEB) and 4,4′,4″,4′′′-pyrazine-2,3,5,6-tetrayl-tetrabenzoate (BTTB).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Lanthanide metal-organic frameworks (LnMOFs) have emerged as an excellent class of luminescent MOFs because of their unique luminescence characteristics, such as sharp line emission bands, a long luminescence lifetime, large Stokes shifts, and incredible emission change behavior in response to a variety of external stimuli. 8,9 Carlos' group was the first to find that the fluorescence intensity of EuMOFs enhanced with increasing pH in the range of 5-7.5. Zhang et al found that the emission intensity of EuMOFs decreased sharply with time under UV lamp irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, organic compounds with variable lifetime have been reported, including thermally activated delayed fluorescence materials 2,27 . However, the challenges associated with controlling the material structure, have limited the rational design of materials with potential for lifetime-encoding 2,3,8,11,28,29 .…”
mentioning
confidence: 99%